COVID-19: the return of football fans. Issue 1 (4th March 2022) - Bond, Alexander John; Cockayne, David; Ludvigsen, Jan Andre Lee; Maguire, Kieran; Parnell, Daniel; Plumley, Daniel; Widdop, Paul; Wilson, Rob
ABSTRACT: COVID-19 has sent a shockwave into society and sport. As result of this, sport and football resuming without spectators - fans or supporters, has brought a number of financial issues that has threatened the sustainability and future of many clubs. This commentary unpicks what has happened and some of the tensions, decision-making and consequences surrounding the return of spectators. The commentary presents the case that spectators are key to the survival of football clubs and that the United Kingdom Government must reverse their decision to not let spectators return. Now more than ever, these words hold substance, meaning and truly matter to clubs and their networked communities, "Football without fans is nothing".